2022
DOI: 10.1055/s-0042-1749073
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Palliative Colonic Stent Placement in Malignant Colonic Obstruction: Experience from a Tertiary Care Oncology Center in India

Abstract: Introduction Colonic self-expanding metal stent (SEMS) placement is the preferred method for palliation of malignant colonic obstruction. We analyzed outcomes of patients who underwent colonic SEMS placement for palliation at a tertiary care oncology center in Western India. Methods Retrospective review of the endoscopy database was done for patients who underwent colonic SEMS placement at our center between January 2013 and September 2021. Demographic details, intent of stent placement, site of obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…9 Sundaram et al reported that colonic self-expanding metal stent achieves good palliation of malignant colonic obstruction in patients. 10 Katrevula et al determined potential role of optical diagnosis using endocytoscopy and endocytoscopy-computer-aided diagnosis to predict histopathological diagnosis of neoplastic diagnosis. 11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies.…”
mentioning
confidence: 99%
“…9 Sundaram et al reported that colonic self-expanding metal stent achieves good palliation of malignant colonic obstruction in patients. 10 Katrevula et al determined potential role of optical diagnosis using endocytoscopy and endocytoscopy-computer-aided diagnosis to predict histopathological diagnosis of neoplastic diagnosis. 11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies.…”
mentioning
confidence: 99%